USAHA KOPRA UNTUK MEMENUHI KEBUTUHAN EKONOMI MASYARAKAT DI DESA WAINIBE KECAMATAN FENALEISELA KABUPATEN BURU - Tomhisa, Megi Erlen; Riry, Johan; Manakane, Susan E (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2023)
Most people in Wainibe Village have been working as copra farmers for a long time. Copra itself is a dried white flesh of the coconut, from which the oil is extracted. This is the main aspect where their finance is relied on. This research aims to identify whether copra farming can fulfill the economic needs of Wainibe people. The study was conducted at Wainibe Village, Fenaleisela District of Buru Regency during August to September 2022. The population was ±100 farmers and the sample was 30% of it, which is 30 farmers. Some variables we used were Harvest, Split, Side, Drying, Packaging, Selling, Production cost, Profit, Primary Needs (food, cloths, house) and Education Needs. Data analysis was copra farming as a business, with several parameters to determine if it is worthy or not. Those parameters are cultivation technique, means used, procedures, and Benefit Cost Ratio (B/C ratio). Based on B/C ratio analysis, it was recognized that the B/C ratio of copra farming is >1. Therefore, it can be concluded that copra farming is feasible to go as financial income